Geoelectrical resistivity survey to determine sliding surface of landslides prone area case study in Ponjong subdistrict Gunung Kidul regency Indonesia - Al Hussein Flowers Rizqi; Oky Sugarbo; Mayang Pitaloka (Institut Teknologi Dirgantara Adisutjipto, 2022)
The research area is located in Ponjong Subdistrict, Gunung Kidul Regency. Ponjong area specific at Tambakromo village is one of potential in landslides disaster since 2011. The outspread information about landslide and mitigation should be done in research area. The aim of this research is to get the subsurface condition and determine of landslide surface based on geoelectrical resistivity in Tambakromo area, Ponjong Subdistrict, Gunung Kidul regency. The method of this research is used geoelectrical survey by using Dipole - dipole configuration. The result of this research is the lithology of sliding surface is claystone – fine tuffaceous claystone with resistivity value of 29.9 ohmmeter based on Dipole – dipole subsurface cross section at Grogol village. The sliding surface could be found at 5 metres to 20 metres underground. At Sumberejo village, based on dipole-dipole subsurface the lithology of sliding surface is claystone – fine tuffaceous claystone with resistivity value of 6.18 to 29.9 ohmmeter at depth of 20 to 25 metres. Based on the regional stratigraphy correlation showed that the claystone or tuffaceous claystone is included in Semilir Formation. This research should be able to held for local government to proved landslide mitigation in research area.